2009
DOI: 10.1080/10937400903094166
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Current Toxicological Concerns on Vanadium Pentoxide and Other Vanadium Compounds: Gaps in Knowledge and Directions for Future Research

Abstract: Vanadium pentoxide (V(2)O(5)) and other inorganic vanadium compounds have recently been evaluated by several occupational exposure limit (OEL) setting (occupational exposure limit, OEL) committees and expert groups in response to the publication of several new studies, including the U.S. National Toxicology Program (NTP, 2002) carcinogenicity study of inhaled V(2)O(5) in rats and mice, which concluded that clear evidence of lung tumors was seen in mice of both genders and that there was some evidence of carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(57 citation statements)
references
References 53 publications
0
56
0
1
Order By: Relevance
“…Genotoxic mechanisms for tumor induction by V 2 O 5 in B 6 C 3 F 1 mice was not supported by the negative results in an Ames assay using Salmonella strains TA1535, 100, 97, 98, and 102 and the lack of evidence of micronucleus induction in peripheral blood from mice exposed to 1-16 mg/m 3 V 2 O 5 by inhalation for 3 months [14,26]. However, recent studies reported a slight increase in 8-oxodGuo DNA lesions in lungs of female B 6 C 3 F 1 mice exposed to 1 or 4 mg/m 3 V 2 O 5 for 16 days by nose-only inhalation [21], and increased micronuclei in peripheral blood in male but not female CD1 mice exposed to 1.4 mg/m 3 V 2 O 5 for 2 h per week for 4 weeks by aerosol inhalation [20].…”
Section: Discussionmentioning
confidence: 98%
“…Genotoxic mechanisms for tumor induction by V 2 O 5 in B 6 C 3 F 1 mice was not supported by the negative results in an Ames assay using Salmonella strains TA1535, 100, 97, 98, and 102 and the lack of evidence of micronucleus induction in peripheral blood from mice exposed to 1-16 mg/m 3 V 2 O 5 by inhalation for 3 months [14,26]. However, recent studies reported a slight increase in 8-oxodGuo DNA lesions in lungs of female B 6 C 3 F 1 mice exposed to 1 or 4 mg/m 3 V 2 O 5 for 16 days by nose-only inhalation [21], and increased micronuclei in peripheral blood in male but not female CD1 mice exposed to 1.4 mg/m 3 V 2 O 5 for 2 h per week for 4 weeks by aerosol inhalation [20].…”
Section: Discussionmentioning
confidence: 98%
“…Among V compounds, V pentoxide is highly toxic [101]. Similar to Ni, the pentavalent forms, such as V and vanadate, have carcinogenic potential via ROS generation, DNA damage, and activation of hypoxia signaling [200]. ROS generation and MAPK phosphorylation have been shown to play important roles in cell cycle arrest induced by vanadate [201].…”
Section: Vanadiummentioning
confidence: 98%
“…Ress et al (2003) noted at the time that tumor incidence rates can be affected by diet, and as a consequence, ''use of the existing historical control database (NIH-07) may not be appropriate for all neoplasms'' (see also Haseman et al, 2003;Assem and Levy, 2009).…”
Section: Introductionmentioning
confidence: 99%